Becoming a Mother in a Strange Land: What cultural care immigrant women experience in Portugal? - Coutinho, Emília de Carvalho; Silva, Alcione Leite; Lopes, Cláudia Sofia Martins Silva; Parreira, Vitória Barros Castro; Duarte, João Carvalho; Nelas, Paula Alexandra Batista; Chaves, Cláudia Margarida Balula; Amaral, Maria Odete (Fronteira: Journal of Social, Technological and Environmental Science, 2014)
A woman who experiences motherhood in the context of immigration is susceptible to mismatches in care, compromising her own experience of pregnancy and childbirth and satisfaction with care. This study intends to understand the traditions, beliefs, and practices of cultural care related to pregnancy, childbirth and postpartum of immigrant mothers in Portugal. It is Qualitative research, using the semi-structured interview in which 60 immigrant mothers participated. Content analysis was supported by NVivo 10. Various beliefs, traditions and cultural practices associated with pregnancy, childbirth or postpartum, from different cultures, are presented. Of special relevance are the bans and prohibitions imposed on the pregnant woman. Overall, immigrant mothers felt their cultural practices were respected without significant cultural conflicts, contributing to the satisfaction with the care received... Keywords: Beliefs; Practices; Cultural Care; Immigration; Maternity.